Pengaruh Financial Literacy, Sosiodemografi, Dan Risk Tolerance Terhadap Pengambilan Keputusan Investasi Di Pasar Modal (Studi Kasus Pada Mahasiswa Generasi Z) - Ningrum, Niken Widya; Mardani, Ronny Malavia; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to identify and analyze how financial literacy, sociodemographics, and risk tolerance affect investment decisions in the capital market. In this study, it uses quantitative research methods. Researchers chose the population taken, namely generation Z students at FEB UNISMA in 2021, totaling 688 students. The sample used was 90 respondents of FEB UNISMA students in the class of 2021 and the results of this study were processed using the SPSS version 16.0 data processing program. The results of this study as a whole meet the test which shows that financial literacy is proven to have a positive and significant effect on investment decision making in FEB UNISMA students, sociodemographics are proven to have a positive and significant effect on investment decision making in the capital market in FEB UNISMA students, risk tolerance is proven to have a positive and significant effect on investment decision making in FEB UNISMA students. Keywords: Financial Literacy, Sosiodemografi, Risk Tolerance, Invesment.